PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN KEPEMILIKAN MANAJERIAL TERHADAP RETURN ON EQUITY (ROE) - Prasica Rudy Artha, 12.05.52.0191; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2016)
The purpose of this study is to know how the influence of size company, leverage and manajerial ownership toward return on equity (ROE). Return on equity (ROE) is a ratio that how much the profit of a company that was compared with a capital is deposited by the shareholders. The measured of ROE is to used net the income formula/equity. The population of this study is 442 manufacture companies was listed in the Bursa Efek indonesia (BEI) of  2012-2014 period. The method that is used in this study is a quantitative research. The sampling that is used in this research is purposive sampling. The sample passes of the criteria  is 118 companies. The method of the collection that is used is secondary data. Is obtainable from the annual report documentation which has been issued by the companies. The data analysis technique is descriptive analysis, test of normality, test of classical assumptions, test of regression is statistic which is aimed to examine hypothesis that have been stated. The result of this study shows that leverage have signifikan influence toward ROE. A while siza and manajerial ownership shows that haven’t signifikan influence toward ROE.  Keywords: Size, Leverage, Manajerial Ownership, Return On quinity (ROE)